Improving Podcast Distribution on Gwanda using PrivHab: a Multiagent Secure Georouting Protocol. - Sánchez-Carmona, Adrián; Robles, Sergi; Borrego, Carlos (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2015)
We present PrivHab, a multiagent secure georouting protocol that improves podcast distribution on Gwanda, Zimbabwe. PrivHab learns the whereabouts of the nodes of the network to select an itinerary for each agent carrying a piece of data. PrivHab makes use of cryptographic techniques to make the decisions while preserving nodes' privacy. PrivHab uses a waypoint-based georouting that achieves a high performance and low overhead in rugged terrain areas that are plenty of physical obstacles. The store-carry-and-forward approach used is based on mobile agents and is designed to operate in areas that lack network infrastructure. The PrivHab protocol is compared with a set of well-known delay-tolerant routing algorithms and shown to outperform them.